TINJAUAN YURIDIS PUTUSAN MAHKAMAH KONSTITUSI (MK) NOMOR 65/PUU-XXI/2023 BERKAITAN DIPERBOLEHKANNYA LEMBAGA PENDIDIKAN DIJADIKAN SEBAGAI TEMPAT UNTUK BERKAMPANYE - Aflina, Dia; Haryono, Dodi; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
This study aims to understand the perspective of Constitutional Court Decision No.65/PUU-XXI/2023 regarding the legality of using educational institutions ascampaign venues. The background of this research is the evolving political andregulatory context involving educational institutions in Indonesia. Prior to thisdecision, strict regulations prohibited the use of educational facilities for politicalcampaigns to preserve the neutrality and integrity of educational institutions asplaces for learning and intellectual development, free from political influence.This research is a normative legal study with a focus on the principle of legaljustice. It uses secondary data sources, including primary, secondary, and tertiarylegal materials. Data collection was performed through literature review, and dataanalysis employed a qualitative method.The findings reveal that the Constitutional Court's decision to permit the use ofeducational institutions for campaigns is based on balancing political expressionfreedom with educational neutrality. The Court concluded that as long aseducational institutions maintain their integrity and are not disrupted by campaignactivities, using these facilities for political purposes does not violate constitutionalprinciples. The implications include potential changes in the dynamics ofeducational institutions, which will need to establish procedures to ensure thatcampaign activities do not affect the learning process. Regulatory adjustments maybe necessary to define limits and mechanisms for campaign implementation ineducational settings.Keywords: Constitutional Court Decision, Educational Institutions, PoliticalCampaigns, Campaign Venues